Effect of iguratimod and methotrexate on RANKL and OPG expression in serum and IL-1Î²-induced fibroblast-like synoviocytes from patients with rheumatoid arthritis - Wang, X. T.; Li, P.; Xu, T. S.; Ding, R.; Zhang, X.; Bi, L. Q. (Cellular and Molecular Biology, 2016)
The receptor activator of nuclear factor ÎºB ligand (RANKL)/receptor activator of nuclear factor ÎºB (RANK)/osteoprotegerin (OPG) system plays a key role in rheumatoid arthritis (RA)-associated bone erosion. The upregulation of the RANKL/OPG ratio promotes bone erosion. The objective of this study is to explore the effects of iguratimod, a small-molecule disease-modifying antirheumatic drug (DMARD), alone or in combination with methotrexate (MTX), on RANKL and OPG expression in RA. We performed an enzyme-linked immunosorbent assay (ELISA) to investigate the modulatory effects of iguratimod, MTX, or their combination on serum RANKL and OPG levels of patients with RA before and after treatment for 12 and 24 weeks. Furthermore, fibroblast-like synoviocytes (FLS) from patients with RA were interleukin (IL)-1Î²-stimulated and then treated with different concentrations of iguratimod, MTX, or both, and RANKL and OPG expressions were investigated by using ELISA, quantitative real-time polymerase chain reaction (qPCR) and western blot analysis. We found that RANKL levels and the RANKL/OPG ratio significantly decreased in both serum and IL-1Î²-induced RA FLS after treatment. Moreover, combination therapy with iguratimod and MTX showed an even stronger inhibition than each drug alone did. Our results suggest that iguratimod and MTX, especially in combination, efficaciously protected against bone erosion by suppressing the production of RANKL.